Book Review: Akwugo Emejulu, (2015) Community Development As Micropolitics: Comparing Theories, Policies and Politics (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
I approached reviewing this book with considerable interest. Having been active in community development in one form or another for about 50 years, I had observed the changing nature of the relationship between what was happening under the umbrella of this term in the USA and that in the UK with both intellectual and practical curiosity. When I first started serious work in community development, (and indeed before that as a postgraduate student), disregarding literature from UK writers who drew on their experience as colonial administrators, most of the literature available to us originated from the USA, dominated by the-then more radical – or so it seemed – methods of Alinsky which challenged the rather more mainstream books which reflected in their authors’ eyes the notion of community development as one of the three methods of social work. Even the two influential reports emanating from the Gulbenkian Foundation had to dig hard to find a significant UK-based canon.